The Role of Reference Services Librarians at the University of Putra Indonesia (UPI) YPTK Library in Meeting the Information Needs of Library Users - Iswadi Syahrial Nupin; Okta Dasril; Beny Adri Yassin (Pustabiblia: Journal of Library and Information Science, 2026)
Reference services are one of the main pillars in organizing academic libraries, especially in helping users find and utilize information effectively. This study aims to describe and analyze the role of reference service librarians at the Universitas Putra Indonesia (UPI) YPTK Library in meeting the information needs of users. The main focus of this study is how librarians carry out their functions as information facilitators, educators, and mediators between users and information sources, both print and digital. The method used in this study is descriptive qualitative with a field study approach. Data were collected through observation, in-depth interviews with librarians and users, and documentation related to reference service activities. The results of the study indicate that librarians at UPI YPTK have a very strategic role in providing information search guidance, helping users use electronic catalogs and databases, and providing reference consultations for academic needs such as final assignments, research, and writing scientific papers. Both informants interviewed by the author were satisfied with the service provided by the reference service librarian. However, this study also found several challenges, such as limited human resources, lack of ongoing training for librarians, and low awareness of users of the existence of reference services. For this reason, it is recommended to improve librarian competence through information literacy training, strengthening service promotion, and developing a technology-based reference service system. Overall, the role of reference service librarians at UPI YPTK is very important in bridging the information needs of users with relevant, accurate, and accountable information sources. This role not only supports academic activities but also encourages the creation of a campus community that is information literate and independent in learning.